SUBSTITUSI EKSTRAK DAUN CINCAU PADA ES KRIM SUSU KEDELAI: PENINGKATAN KUALITAS DAN POTENSINYA DALAM INDUSTRI PANGAN - Efian, Muhammad Ilham; Mustika, Sari; Elida, Elida; Anggraini, Ezi (Ensiklopedia of Journal, 2025)
Abstract: The demand for healthy and natural food products continues to increase in line with consumer awareness of healthier and more environmentally friendly diets. One of the innovations in the food industry is the use of soy milk as an alternative to cow's milk and the addition of natural ingredients such as grasshopper leaf extract. This study aims to examine the effect of grasshopper leaf extract substitution on the organoleptic quality of soy milk-based ice cream. We carried out substitution by varying the concentration of grasshopper leaf extract to 0%, 25%, 50%, and 75%. The parameters analyzed included color, aroma, texture, sweetness, and typical taste of grasshopper leaves through an organoleptic test involving 50 panelists. The results showed that the substitution of grasshopper leaf extract had a significant influence on the quality of the color, aroma, texture, and distinctive taste of grasshopper leaves, with a concentration of 75% producing the best quality. On color parameters, the concentration of 75% extract increased the intensity of the green color (average value 5.60). Meanwhile, texture and aroma also showed a significant increase with values of 5.25 and 5.21, respectively. Although not significant, the sweetness slightly increases at higher concentrations. The content of compounds in grasshopper leaves, such as chlorophyll, flavonoids, and tannins, contributes greatly to the organoleptic characteristics of ice cream. These results show that grasshopper leaf extract has the potential as a natural ingredient to improve the quality and functional value of soy milk-based ice cream products, as well as support the trend of healthy and environmentally friendly food innovation.Keywords: Cincau Leaves, Soy Milk Ice Cream, Organoleptics, Food Innovation, Functional Products.